Enhancing the supercapacitive performance of soot material induced with manganese cobaltite (MnCo2O4) for supercapacitor application - Stephen A. Darko; Shambach T. Puplampu; Daniel Yeboah; K. Mensah-Darkwa (Next Materials, 2025)
Processing waste carbonaceous materials into useful products presents a sustainable alternative to its recovery. An effective and environmentally benign way of reusing such waste is to convert them into electrodes capable of supporting energy conversion reactions. This study introduces a cost-effective synthesis of a composite electrode for supercapacitor application using a waste carbonaceous soot obtained from Tema Steels Limited, a local steel manufacturing company in Ghana, having it subjected through thermal treatment at 500 °C and synergizing with annealed MnCo2O4 to augment the soot’s supercapacitive capabilities. The fabricated composite electrode comprises treated (thermally activated) soot combined with annealed MnCo2O4 material in 1:1 mass ratio, using a facile hydrothermal synthesis technique. Halogen like chlorine negatively affect the supercapacitive performance of soot, the as-received soot was subjected to a 500°C, 2-hour thermal treatment to optimize its performance, effectively reducing chlorine content from 4.1 to 2.1 at. weight percent and notably augmenting its specific surface area (SSA). SSA increased from 183.3 m2g−1 to 253.3 m2g−1, a 27.6 % increment after thermal treatment. The electrode’s supercapacitive performance was utilized using a 3 M KOH electrolyte solution employed in a three-electrode system. Attaining a current density of 3Ag−1, the composite electrode achieved a specific capacitance of 2818 Fg−1. The fabricated composite electrode demonstrated a stable charge/discharge capability by retaining around 87 % of its capacity after 10,000 cycles, establishing its practicality for applications in electrochemical storage.